Natural products can efficiently control the greater wax moth (Lepidoptera: Pyralidae), but are harmless to honey bees - Telles, D. M. [UNESP]; Martineli, G. M. [UNESP]; Scaloppi, M. F. [UNESP]; Da Luz, M. P. Ferreira [UNESP]; Kadri, S. M. [UNESP]; Orsi, R. O. [UNESP] (Universidade Estadual de Feira de Santana, 2020)
Honey bees (Apis mellifera L.) have great global socioeconomic and environmental importance. However, the greater wax moth (Galleria mellonella L.) is a pest that causes serious worldwide damage to honey bee colonies. Good beekeeping practices and physical, chemical, or natural methods can be used to control wax moths. The use of natural products is a more sustainable option because of their lower toxicity to the environment and the colony. Therefore, we evaluated the efficiency of four natural products for greater wax moth control: neem oil (Azadirachta indica), eucalyptus oil (Eucalyptus spp.), tobacco extract (Nicotiana tabacum), and malagueta pepper extract (Capsicum frutescens). We also evaluated their effects on adult bees and on the population growth of colonies. The 4th instar wax moths and adult bees were subjected to in vitro bioassays of different concentrations of the products. The results allowed us to establish a concentration for each product that was safe for the bees and effectively controlled the moth. Then, we sprayed them on bee colonies to evaluate their effects on population growth. The neem and eucalyptus oils caused wax moth mortality at low concentrations, but did not affect colony population growth. However, they did have a toxic effect on adult bees. The tobacco and pepper extracts efficiently controlled the moth, but did not cause adult bee mortality or interfered with the population growth of the colonies. Therefore, the tobacco and pepper extracts could efficientlycontrol the greater wax moth, without damaging honey bees.
Keywords: Beekeeping; Natural methods; Pest